Economic and social inequality in Thailand: Causes, impacts, and solutions - Bunwong, Suntorn (Thai Social Science Journal, 2026)
This article aims to analyze the main causes, impacts, and solutions to economic and social inequality in Thailand, a persistent problem significantly affecting the country’s development in multiple dimensions. The study finds that the unbalanced economic structure between the agricultural and industrial sectors, along with unequal access to education and social welfare, are key factors driving the continuous expansion of inequality. The article highlights the wide-ranging consequences of inequality, including slowed economic growth, social conflict and instability, and restricted opportunities for education and workforce skill development among disadvantaged groups, which are major obstacles to sustainable national development. To address these issues, the article proposes policy reforms focusing on fair income distribution, improving equitable access to education and welfare systems, and promoting collaboration among government, private sector, and civil society to foster fairness and reduce inequality at the grassroots level. This article hopes to contribute to stimulating serious policy and social change, preventing inequality from undermining Thailand’s future and building a more equitable and sustainable society in the long term.